2009
DOI: 10.1016/j.intcom.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

An integrative approach to requirements analysis: How task models support requirements reuse in a user-centric design framework

Abstract: a b s t r a c tMany software systems fail to address their intended purpose because of a lack of user involvement and requirements deficiencies. This paper discusses the elaboration of a requirements-analysis process that integrates a critical-parameter-based approach to task modeling within a user-centric design framework. On one hand, adapting task models to capture requirements bridges the gap between scenarios and critical parameters which benefits design from the standpoint of user involvement and accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In contrast to the activity-centric scenario and other approaches (Oliver et al 2006;Dragunov et al 2005;Dredze et al 2006;Montabert et al 2009), here, activity labeling is a subjective matter. Because activities are corrected and labeled by the owner of the data, i.e., the user him-or herself, this user-provided ground truth data is used to train the system and a test is performed later on the activity data of the same user.…”
Section: Window Captionmentioning
confidence: 96%
“…In contrast to the activity-centric scenario and other approaches (Oliver et al 2006;Dragunov et al 2005;Dredze et al 2006;Montabert et al 2009), here, activity labeling is a subjective matter. Because activities are corrected and labeled by the owner of the data, i.e., the user him-or herself, this user-provided ground truth data is used to train the system and a test is performed later on the activity data of the same user.…”
Section: Window Captionmentioning
confidence: 96%
“…In a study employing integrative approach to requirements analysis in a usercentric design framework, [5] pointed out the lack of consistency among designers could be an important reason leading to the limited usefulness of the designed system. There exist many reasons that may possibly lead to the illdefined usability/UX requirements, such as constantly changing instructions, vague user needs, budget concerns, and time constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the major causes of project failure are requirements inconsistencies and missing user involvement ( [1], [6], [9]). As [1], [5] and [7] stressed, user involvement is a critical factor in the product development process. We should get users involved from the very beginning of the project until the end of it: getting their ideas to better understand their requirements and needs before we design the product, getting their experience of the prototype, and asking them to test the final product and give us their feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally conducting a requirements analysis was an early step in the waterfall approach to software development [3,4,5]. However, "agile" approaches which include user and stakeholder involvement throughout development [6] and recognise the need for flexibility and change [7] have been used more and also combined with the waterfall approach.…”
Section: Introductionmentioning
confidence: 99%